A cross-sectional study on the association between farmers' awareness and compliance on herd health program among five selected dairy cattle farms in Selangor and Negeri Sembilan states, Malaysia - Abdullah, Faez Firdaus Jesse; Sadiq, Muhammad Abubakar; Abba, Yusuf; Ropie, Abdul Muhaimin; Mohammed, Konto; Lim, Eric Teik Chung; Bitrus, Asinamai Athliamai; Mat Isa, Noor Hanani; Mohd Lila, Mohd Azmi; Haron, Abd Wahid; Saharee, Abdul Aziz (Department of Veterinary Services Malaysia, 2017)
A cross-sectional study was designed to determine the level of awareness of selected dairy farmers to herd health program (HHP) and compliance in the Program Ladang Angkat (PLA). The study also determined the association between farmers’ awareness and compliance in promoting herd health. An open-ended questionnaire was randomly administered to five dairy cattle farms within Selangor and Negeri Sembilan as representative dairy farms enlisted into the PLA of Faculty of Veterinary Medicine, Universiti Putra Malaysia. The mean herd size of the farms was 102.20±20.80, with a range of 30-160 heads of dairy cattle, having an average mean number of milking cows at 29.40±11.22. There was a higher (p<0.05) mean herd health awareness level (72.86±5.78%) among the farmers once compared with the mean compliance level (61.2 ± 4.1%) for 10 out of the 14 HHP components; with the lowest compliances being disease monitoring programme (33.20%) and biosecurity (39.9%). There was a significant (p<0.05), direct, weak positive correlation (r = 0.245; p = 0.042) between farmers’ awareness and farmers’ compliance to the 14 components of the HHP. This study highlights an appreciable level of awareness among dairy farmers in the PLA, with a relatively low compliance levels to the HHP components.